Visitor satisfaction on ecotourism site model - Sapari, Mohamad Safee; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (Faculty of Forestry, Universiti Putra Malaysia, 2013)
Ecotourism development has been given serious attention by the government of Malaysia. The government has invested huge amounts of money to develop infrastructure and services at various ecotourism sites to attract tourists. The objective of the study is to determine the satisfaction level of tourists who visit the Kilim Karst Geoforest Park (KKGP), Langkawi. The modification model (ECOSERV), adapted from the SERVQUAL model and Expectancy Disconfirmation Theory EDT is used as a framework in this study which includes the eco-tangible dimension to better explain the context of the ecotourism site. The satisfaction level is measured by evaluating the gaps between tourist expectation and perceived value. The level of satisfaction can be determined from differences between expectation and perceived performance whereas when the expectation is greater than perceived performance, it means the visitor is not satisfied. If perceived performance meets expectation this indicates that the visitor is satisfied. Many variables may influence visitors’ satisfaction, which may include services, price, environment, attraction, culture and climate and image. The sample population for this study consists of visitors of KKGP. The cluster sampling technique was used for local and international visitors at KKGP.